Letter - Lizaso, Jose I. de
013-0035-001 Euzkadi Ordezkaritza Basque Delegation, 7/8 Hobart Place, Eaton Square, London S.W.1. Tel: SLOANE 4359 29th August, 1941. Dear Mr Carthy, I have been considering the question you raised this afternoon, asking us to make some inquiries as to the whereabouts of Harry Graham, a member of the International Brigade. Before doing so, I should very much like to have a few more details, which perhaps you could obtain from his wife in Belfast. Data which would help me a lot would be: the date when he joined the International Brigades; the company, battalion or division in which he was serving, together with his rank; and also the names and nationality of some of the officers or men who were friends of his. It would also assist if we knew whether he joined under his own name or some other. When I have these details, I shall be, as I told you this afternoon, pleased to do my best to find out indirectly, through the International Bridage Association, what has happened to him. As I told you, we have no direct contact with this body. If we cannot find out anything from them, I shall approach the International Red Cross, because I know that they have a list of members of tne International Brigade in France. In any case I will do my best to help you. Yours sincerely Jose I. de Lizaso pc att sent 1/9/41 A. E. Carthy, Esq. Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/13/35